Radicalism and Terrorists: Analyzing the Development of ISIS Thought - Hambaliana, Dandie; Alfahmi, Ibrahim NH; Suprianto, Sopian; Arsyad, M Fikri; Gibran Lubis, Ahmad Khomeini Ali (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to analyze the history of the development of ISIS thought as one of the most significant radical and terrorist groups in the 21st century. The study traces the ideological roots of ISIS, including the influence of Salaf-Jihadi ideology, as well as how the group selectively uses religious literature to legitimize its actions. With a historical and multidisciplinary approach, this study uncovers the political, social, and economic factors that supported the emergence and development of ISIS, especially after the United States invasion of Iraq in 2003. The results of the analysis show that ISIS's thinking is not only rooted in extreme religious interpretations, but also influenced by geopolitical chaos, political marginalization, and the failure of local governments in the Middle East region. This study emphasizes the importance of understanding the ISIS phenomenon holistically to design effective strategies in preventing radicalism and terrorism in the future.